Direct access surgery for cholecystectomy – can we speed up the process?. Issue 3 (March 2020) - Burton, Thomas; Rossaak, Jeremy
Abstract: Background: In appropriate patients, direct referral from general practitioners to surgery without pre-operative clinic assessment can streamlining the process and allow more efficient use of clinical time. This study aimed to look at the feasibility of a direct access cholecystectomy pathway in patients with symptomatic gallstones and their satisfaction of it. Methods: In 2012, Bay of Plenty general practitioners (GP) were invited to refer fit patients (ASA 1 or 2, BMI <35 and <60 years old) with symptomatic cholelithiasis directly to a surgical list. One surgeon oversaw each referral and the process. The patients GP provided written and visual information and pre-operative health preoperative health questionnaire. Patients presented on the day of surgery, were seen, consented and underwent day stay cholecystectomy. Post-operative follow up was GP lead. Results: 41 patients were referred via the Direct Access Surgery pathway. 37 patients were deemed appropriate with 35 proceeded to surgery. Waiting time from referral to operation was reduced from 120 (standard pathway) to 59.3 days. 30 patients (86%) had day stay procedures. Three patients (8%) re-presented with ongoing right upper quadrant pain within one year requiring further investigation. A written voluntary questionnaire was sent to all patients who underwent DAS with an 80% response rate. Overall the majority of patients (24/28; 85%) agreed or strongly agreed that they felt fully informed regarding the operation and were happy with the process. Conclusion: Direct Access Surgery is an effective way to streamline healthy patients' access to operative intervention.